2016
DOI: 10.1038/srep21123
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Liposome Membrane Permeability by Competitive Peptide Dimerization and Partitioning-Folding Interactions Regulated by Proteolytic Activity

Abstract: Membrane active peptides are of large interest for development of drug delivery vehicles and therapeutics for treatment of multiple drug resistant infections. Lack of specificity can be detrimental and finding routes to tune specificity and activity of membrane active peptides is vital for improving their therapeutic efficacy and minimize harmful side effects. We describe a de novo designed membrane active peptide that partition into lipid membranes only when specifically and covalently anchored to the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…2a). 42-residue polypeptides JR2EC and JR2KC (helix-loop-helix motifs) were used 46,51. As shown by circular dichroism (CD) spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2a). 42-residue polypeptides JR2EC and JR2KC (helix-loop-helix motifs) were used 46,51. As shown by circular dichroism (CD) spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al ( 60 ) proposed that HLH proteins possess a cell penetration property and the internalization mechanism would be primary by a type of macropinocytosis. In addition, it has been already reported that a pharmacological molecule with an HLH structure may fuse to the cell membrane or perform a membrane pore entering in this way into the cell ( 61 ). Once in the cell, GAP activity could be directly supported by its HLH motif, via binding of calcium, a major intracellular messenger ( 62 ), or via heterodimerization with other HLH-regulatory factors involved in gene transcription ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes were prepared according to methods that are well established in the field [ 17 , 18 ]. Briefly, liposomes were prepared by dry film formation, hydration and finally extrusion through a polycarbonate membrane to form monodisperse large unilamellar vesicles.…”
Section: Methodsmentioning
confidence: 99%